Examining the Significant Factors Inhibiting Agricultural Sector Growth during COVID-19 Pandemic in Indonesia - Wiranatakusuma, Dimas Bagus; Fairuztama, Rafif; Saputra, Jumadil (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2025)
The agricultural sector has emerged as a critical economic pillar in Indonesia. Limited research has been conducted on Indonesia's agricultural development. However, there exists a body of literature that thoroughly integrates the agricultural sector with banking and the macroeconomic environment, especially in the context of the period preceding and during the covid-19 pandemic. This study seeks to explore various factors that hinder the growth of the agricultural sector by examining specific banking and macroeconomic variables. This research employs quarterly data from 2010 to 2024 and analyzes it utilizing a multiple regression methodology. In pursuit of this objective, the analysis incorporates the growth of agriculture's GDP share relative to total GDP, the financing of agriculture alongside total time deposits in Islamic banks, the margin of Islamic banks within the agricultural sector, the relationship between agriculture's financing and GDP, as well as considerations of inflation and food prices. Empirical evidence indicates that only financial deepening (GCPGDPP) and banking intermediation (GFinPDT) have a significant impact on agricultural growth (GGDPRGDPT). An increase in financial deepening adversely affects growth. This discovery suggests that the agricultural sector in Indonesia requires enhancements in productivity, necessitating the advancement of professional managerial skills and the adoption of technology among farmers. Furthermore, considering the considerable influence of banking intermediation on agricultural growth, it is essential that financial deepening is aligned with entrepreneurial skills capable of producing high-value-added products. The study presents a significant contribution to the growth of the agricultural sector in Indonesia by highlighting the importance of enhancing banking sector financing alongside the development of improved professional managerial skills within the agricultural industry.